Quantitative disease resistance: to better understand parasite-mediated selection on major histocompatibility complex - Westerdahl, Helena (The Royal Society, 2012)
We outline a descriptive framework of how candidate alleles of the immune system associate with infectious diseases in natural populations of animals. Three kinds of alleles can be separated when both prevalence of infection and infection intensity are measured—qualitative disease resistance, quantitative disease resistance and susceptibility alleles. Our descriptive framework demonstrates why alleles for quantitative resistance and susceptibility cannot be separated based on prevalence data alone, but are distinguishable on infection intensity. We then present a case study to evaluate a previous finding of a positive association between prevalence of a severe avian malaria infection (GRW2, Plasmodium ashfordi) and a major histocompatibility complex (MHC) class I allele (B4b) in great reed warblers Acrocephalus arundinaceus. Using the same dataset, we find that individuals with allele B4b have lower GRW2 infection intensities than individuals without this allele. Therefore, allele B4b provides quantitative resistance rather than increasing susceptibility to infection. This implies that birds carrying B4b can mount an immune response that suppresses the acute-phase GRW2 infection, while birds without this allele cannot and may die. We argue that it is important to determine whether MHC alleles related to infections are advantageous (quantitative and qualitative resistance) or disadvantageous (susceptibility) to obtain a more complete picture of pathogen-mediated balancing selection.